Dual‐band notched ultra‐wideband antenna by using step‐by‐step design inside conductor‐backed plane. Issue 5 (23rd March 2013) - Esmati, Zahra; Moosazadeh, Mahdi
Abstract A coplanar waveguide fed (CPW‐fed) ultra‐wideband antenna with dual band‐notched characteristics is proposed. The main features of the proposed antenna are the compact dimensions and band‐notched characteristics that are achieved without modifying the radiator or the CPW‐ground plane. Dual band‐notched characteristics are achieved by M‐shaped strip inside the slotted conductor‐backed plane. Also, wider impedance bandwidth can be achieved with this structure. The measured results show that the proposed antenna operates over the frequency band between 2.6 GHz and 11.7 GHz (127%), defined by VSWR < 2, except two notched bands (3.25–4.32 GHz and 5.02–5.97 GHz), where the VSWR is more than eight, aimed at suppressing any interference from IEEE802.16 WiMAX (3.3–3.6 GHz), C‐band (3.7–4.2 GHz), and IEEE802.11a WLAN (5.15–5.825 GHz). The designed antenna has a small size of 15 × 15 mm2. The antenna has a desirable VSWR level, radiation pattern and gain characteristics for ultra‐wideband frequency band range. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1069–1074, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27512